Analyzing and Classifying Risks Arising During Innovation Project Implementation in Aircraft Motor-Building - T. B. Timofeeva; E. A. Ozdoeva (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
The current Strategy of Innovative Development of the Russian Federation for the period up to 2020 and the Strategy of Scientific and Technological Development of the Russian Federation determine the goals, priorities and objectives of the state innovation policy and scientific and technological development of the country. A significant role is given to areas that allow us to obtain scientific and technical results that are the basis for increasing the innovative level of production and consolidating the country's position in the foreign market. Among the priority areas is the aviation industry, namely the sector of aircraft engine construction. The creation of aircraft engines is currently one of the most science-intensive and high-tech tasks of the domestic aircraft industry. However, the analysis of the current state of implementation of programms in this area shows that the problems of their functioning and development are not always solved taking into account a wide range of emerging risks, the negative impact of which can lead to significant financial losses. To develop effective methods for assessing and minimizing risks, it is necessary to first analyze and classify them. In the article, based on the analysis, a system of classification of risks arising during development aircraft engines. The results obtained will allow us to give a preliminary qualitative assessment of the negative events that occur at various stages of the development of aircraft engines.